Temporal variations of geoid heights over Kazakhstan from GRACE–FO data and their relation with hydrological changes in the Caspian Sea and seismic activity - Shoganbekova, Daniya; Urazaliyev, Asset; Godah, Walyeldeen; Nurakynov, Serik; Zhaksygul, Nailya; Kozhakhmetov, Magzhan (Frontiers in Earth Science, 2025)
IntroductionWe quantify temporal variations of geoid heights (ΔN) across Kazakhstan during 2019–2024 using satellite gravimetry, and relate these changes to recent extreme hydrological and seismic events.MethodsMonthly ΔN fields were derived from GRACE-FO–based global geopotential models. We applied seasonal-trend decomposition to isolate seasonal and long-term components, mapped linear trends, and assessed 2024 mass-change anomalies. Consistency checks included correlations with Caspian Sea water-level records and a preliminary comparison between ΔN and ellipsoidal height changes from five continuous GPS stations within the study area.ResultsΔN exhibits a clear seasonal cycle with amplitudes up to ∼3.5 mm. A persistent decline in geoid heights during 2019–2022 is observed along the Caspian Sea coast, reaching rates of up to −1.57 mm yr−1. In 2024, mass anomalies associated with seismic and hydrological events interrupted this decline. ΔN correlates strongly with Caspian Sea level variations (r = 0.91). GPS–GRACE-FO comparisons show an inverse seasonal pattern, consistent with mass-loading effects.Discussion/conclusionsGRACE-FO robustly captures regional, mass-related geoid variability over Kazakhstan. The results support applications in geodetic infrastructure maintenance, hazard assessment and early warning, and climate-impact analysis. They also provide inputs relevant to the realization of the International Height Reference Frame by accounting for time-variable gravity in Central Asia.